2011
DOI: 10.1108/13563281111186931
|View full text |Cite
|
Sign up to set email alerts
|

How readable are mission statements? An exploratory study

Abstract: PurposeMission statements are fairly ubiquitous, particularly among large organizations. However, if they are to have a chance of achieving the desired positive outcomes, they must first be readable and comprehensible to the targeted stakeholders. The purpose of this paper is to investigate this issue, to answer the question of whether the mission statements of large companies are readable or not.Design/methodology/approachContent analysis and appropriate scores were employed to investigate the readability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 27 publications
2
69
0
Order By: Relevance
“…The PMSB construct represents organisation strategic alignment to the mission statement. There are no surprises here as the results support past studies which indicated the importance of mission statement clarity for organisational strategic alignment Bart, 1997;Desmidt et al, 2011;Sattari et al, 2011;Stone, 1996) and strategic alignment is positively linked to organisation outcomes (Braun et al, 2012;Koon, 2015). Furthermore, the results indicate that strategic alignment contributes positively towards a fit situation which is in line with Guest (1994) who suggested that human resource practices like recruitment, orientation and training can contribute towards sustaining shared norms and values.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The PMSB construct represents organisation strategic alignment to the mission statement. There are no surprises here as the results support past studies which indicated the importance of mission statement clarity for organisational strategic alignment Bart, 1997;Desmidt et al, 2011;Sattari et al, 2011;Stone, 1996) and strategic alignment is positively linked to organisation outcomes (Braun et al, 2012;Koon, 2015). Furthermore, the results indicate that strategic alignment contributes positively towards a fit situation which is in line with Guest (1994) who suggested that human resource practices like recruitment, orientation and training can contribute towards sustaining shared norms and values.…”
Section: Discussionsupporting
confidence: 87%
“…Past studies have shown that clarity in the mission statement (MC) is important for alignment of organisational arrangements (Bart, Archer, & Ghasemzadeh, 1998;Bart, 1997;Sattari, Pitt, & Caruana, 2011;Stone, 1996). The perception of mission statement clarity by key managers who are directly involved in managing business and people is important because managers play an active role in the strategic and cultural alignment of the organisation with the mission statement.…”
Section: Strategic Alignmentmentioning
confidence: 99%
“…The regulation to enhance "Plain English" is to ensure that companies use clear language, avoid vague language to hide negative information, and ensure that all investors can understand disclosures and make informed decisions (Li, 2008). Readability is the cornerstone of understandability, since a document that is easy to read facilitates comprehension, retention, reading speed, and reading persistence (Sattari, Pitt, & Caruana, 2011). The SEC handbook on plain English writing alludes to six principles, namely short sentences, everyday language, active voice, tables and bulleted lists where possible, not legal or business jargon, and no double negatives (Li, 2008).…”
Section: Readabilitymentioning
confidence: 99%
“…Results are mixed as to whether or not mission statements actually influence an organization's performance (Sattari et al 2011;Williams 2008). Some mission statements are too vague, irrelevant, unrealistically inspirational, not truthful or representative, or unreadable.…”
Section: Mission Statements and Guiding Principlesmentioning
confidence: 98%